Animasi Motion Graphic Safety Induction di Wilayah Universitas Pembangunan Nasional “Veteran” Jawa Timur untuk Mencegah Terjadinya Kecelakaan Kerja - Aulia Devi Rachmania (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Institut Desain dan Bisnis Bali, 2023)
Workplace accidents in Indonesia are a significant problem, with increasing incidents each year. This can adversely affect productivity in addition to resulting in fatalities and material losses. A good culture of Occupational Health and Safety (OHS) is necessary to reduce workplace accidents. One way to implement an OHS culture is through the implementation of safety induction. Universitas Pembangunan Nasional